2007
DOI: 10.1111/j.1600-6143.2006.01686.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Poor Graft Outcome in Patients with Antibody-Mediated Acute Rejection

Abstract: This study analyzes the incidence and course of antibody-mediated rejection (AMR) in a cohort of 237 renal transplant patients followed for 30 ± 20 months. Among these, 32 patients were considered to be at risk for AMR and received intravenous immunoglobulin (IVIg), either as preconditioning (Group A, n = 18) or at the time of transplant (Group B, n = 14). The prevalence of AMR was 27.8% in Group A, 57.1% in Group B and 3.9% in the remainder of the population. Although graft loss remains greater among AMR than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
99
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(107 citation statements)
references
References 47 publications
7
99
0
1
Order By: Relevance
“…Explaining "the Paradox" of Frequent Accommodation and Low Prevalence of Anti-HLA Antibodies Anti-HLA antibodies are generally considered detrimental for organ transplants, and the presence of these antibodies in the blood of a transplant recipient predicts rejection [17][18][19][20]. Consistent with this concept, anti-HLA antibodies are detected infrequently in those with normally functioning transplants.…”
Section: Accommodation In Clinical Transplantationsupporting
confidence: 54%
“…Explaining "the Paradox" of Frequent Accommodation and Low Prevalence of Anti-HLA Antibodies Anti-HLA antibodies are generally considered detrimental for organ transplants, and the presence of these antibodies in the blood of a transplant recipient predicts rejection [17][18][19][20]. Consistent with this concept, anti-HLA antibodies are detected infrequently in those with normally functioning transplants.…”
Section: Accommodation In Clinical Transplantationsupporting
confidence: 54%
“…In a 2007 study of biopsies for clinical rejection in confirmed AMR, we found v1 and v2 in 33.3 and 23.8% of patients at first biopsy, respectively. 22 Furthermore, we found that v1-v2 was closely correlated with signs of AMR (glomerulitis, PTC) and that the tubulitis expected with ACR was totally absent in 12/25 cases. We suggested on the basis of these findings that intimal vasculitis could be a manifestation of AMR rather than simply concomitant ACR.…”
Section: Relationship Of Arteriosclerosis To Vasculitic (V1 and V2) Lmentioning
confidence: 70%
“…Conventional assessment permits to diagnose ABMR but is insufficient for prediction of outcome and risk assessment in patients with ABMR. 17 Our hypothesis is that the ABMR Molecular Score and the endothelial transcripts reflect active remodeling of the microcirculation because of relatively recent antibody-mediated damage, implying the action of the antibody and its effector mechanism, and thus, can be used as a companion to the conventional features, such as histopathology. The ABMR Molecular Score is the weighted average of a larger set of genes selected using a simple t test comparing two classes of biopsies and then fine tuned using linear discriminant analysis, whereas the endothelial DSA-selective transcripts score is the unweighted average of a gene set selected using domainspecific knowledge of transplant biology.…”
Section: Discussionmentioning
confidence: 99%